Dynamic characterization of fibre reinforced composite (S-Glass) in rigid armoured vehicle / Abd Halim Idris - Idris, Abd Halim (2006)
The advent of high strength and light weight composite materials and newly developed resin materials have radically changed the concepts of advanced space structure and Armoured vehicles [I]. This high strength - to-weight or modulus-to-weight ratios of composites could also result in lighter structural components with lower operating costs and better maintenance history. Since, most current space structures , unmanned vehicles, aircraft structures and high performance defence vehicles are designed to be robust ; designers have been quick to realize the advantages of this advanced material. In response to this, the United State Army Tank-Automotive Command (TACOM) had been evaluating alternative lighter weight materials such as titanium alloys and ceramic tile/polymer-matrix composites (PMCs) that are currently the only practical possibilities for lighter-weight structural armour applications [2]. The alloys do have disadvantages when a spall liner] is required that there are relatively to fabrication example machining and welding. Although PMCs offer some advantages for example freedom from spalling against chemical threats, a quieter operator environment and a high mass efficiency against ball and fragment ballistic threats. Nevertheless, spall liners have been identified as providing improved protection for the tank crews but they still have a number of problems.